Stability of the static-fluid cylindrical regular spacetime - Mazharimousavi, S. Habib (Academic Press Inc Elsevier Science, 2023)
In this paper, we study the mechanical stability of a static cylindrically symmetric regular solution to Einstein's field equations that is supported by a static uniform perfect fluid with the equation of state p = - 13 epsilon in which p and epsilon are the pressure and the energy density of the uniform and isotropic perfect fluid. With the line-element ds2 = -dt2+sech2 (xi p) +xi 12 sinh2 (xi p) d phi 2), this spacetime contains only one parameter, namely, xi = 3 such that for small p or xi -> 0 limit, the spacetime becomes flat. This solution belongs to a class of solutions found long ago by Bronnikov in the context of a static cylindrically symmetric perfect fluid, however, its interesting properties have not been noticed previously. Particularly, we show that this special cylindrically symmetric solution to the Einstein equations describes a regular distribution of gas of disordered cosmic strings. Moreover, with detailed calculations, we prove that the spacetime is unstable against a radial linear perturbation of its perfect fluid source. (c) 2023 Elsevier Inc. All rights reserved.
Keywords: Mechanical stability; Uniform string; Exact solution; Perfect fluid